TECHNOLOGY FOR OBTAINING MILK SUGAR FROM SECONDARY MILK RAW MATERIALS (British Journal of Global Ecology and Sustainable Development, 2022)
The rational use of secondary raw materials on the principles of resource and energy saving is one of the most urgent tasks of the food and processing industries of the agro-industrial complex. In the dairy industry, the problem of effective whey processing is traditionally most acute, in particular, the maximum extraction of dry substances (up to 50% of the initial concentration in milk) - lactose (the main carbohydrate of milk), biologically complete whey proteins, vitamins and other biogenic elements. In the last decade in foreign countries with the most developed dairy business, much attention has been paid to the directed synthesis of derivative components of dairy raw materials (primarily lactose and whey proteins), the inclusion of which in food formulations gives them additional biological value and functional properties.